Simple prescription for computing the nonrelativistic interparticle potential energy related to dual models - De Gracia, G. B. [UNESP]; De Brito, G. P. (World Scientific Publishing, 2016)
Following a procedure recently utilized by Accioly et al. to obtain the D-dimensional interparticle potential energy for electromagnetic models in the nonrelativistic limit, and relaxing the condition assumed by the authors concerning the conservation of the external current, the prescription found out by them is generalized so that dual models can also be contemplated. Specific models in which the interaction is mediated by a spin-0 particle described first by a vector field and then by a higher-derivative vector field, are analyzed. Systems mediated by spin-1 particles described, respectively, by symmetric rank-2 tensors, symmetric rank-2 tensors augmented by higher derivatives and antisymmetric rank-2 tensors, are considered as well.
Keywords: dual models; Interparticle potential energy